2023
DOI: 10.1038/s41467-023-36257-x
|View full text |Cite
|
Sign up to set email alerts
|

A subset of antibodies targeting citrullinated proteins confers protection from rheumatoid arthritis

Abstract: Although elevated levels of anti-citrullinated protein antibodies (ACPAs) are a hallmark of rheumatoid arthritis (RA), the in vivo functions of these antibodies remain unclear. Here, we have expressed monoclonal ACPAs derived from patients with RA, and analyzed their functions in mice, as well as their specificities. None of the ACPAs showed arthritogenicity nor induced pain-associated behavior in mice. However, one of the antibodies, clone E4, protected mice from antibody-induced arthritis. E4 showed a bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 77 publications
1
22
0
Order By: Relevance
“…In addition, He at al. showed that CAIA was prevented by co-injection of an ACPA targeting citrullinated alpha enolase (citENO1) 21 . This effect was mediated by the interaction between immune complexes of ACPA-citENO1 and FCGR2B in macrophages, which promoted IL-10 secretion and reduced osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, He at al. showed that CAIA was prevented by co-injection of an ACPA targeting citrullinated alpha enolase (citENO1) 21 . This effect was mediated by the interaction between immune complexes of ACPA-citENO1 and FCGR2B in macrophages, which promoted IL-10 secretion and reduced osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, these findings support a pathogenic role for ACPAs in arthritis. In contrast, it was recently reported that recombinant ACPAs ameliorated disease symptoms in collagen-antibody induced arthritis (CAIA) 20,21 , and in CIA and various models of neutrophil extracellular trap-(NET) mediated diseases 22 , suggesting that ACPAs can be protective in arthritis.…”
Section: Introductionmentioning
confidence: 99%
“…22 Studies have shown that the destruction of enzyme balance in the body is an important factor in inducing arthritis, especially the increase of matrix metalloproteinase level and the decrease of endogenous antioxidant enzyme expression, which are also related to joint injury, overuse and acquired high-purine diet. [23][24][25][26] At present, various forms of arthritis have been extensively studied and characterized. Noninflammatory arthritis (osteoarthritis, OA) and inflammatory arthritis (such as rheumatoid arthritis, RA) are two dominant joint disorders.…”
Section: Introductionmentioning
confidence: 99%
“…The emerging view for this field is that posttranslational citrullination is sufficiently complex to inspire the term "citrullinome" to describe the many proteins with this modification along with a similar complexity expected in the population of ACPA generated. Indeed, now, in addition to studies identifying ACPA with pathogenic properties (7), we are beginning to see the first hint of protective ACPA (8). Much more work will be needed to establish whether ACPA is solely a biomarker of early RA in humans or whether these autoantibodies actively contribute to disease progression.…”
mentioning
confidence: 99%
“…Arthritogenic ACPA clones might exist but are yet to be identified in RA. Alternatively, analyzing autoantibodies in the right context may be the clue to reveal their pathogenicity, for example, a combination of ACPAs with certain arthritogenic stimuli synergistically increased inflammation in some experimental models (7,8).…”
mentioning
confidence: 99%